Case Report: A balloon-based technique to remove a pearl-like embolus out of the coronary artery - Wu, Kaimin; Chen, Xiang; Ding, Licheng; Wang, Bin (Frontiers in Cardiovascular Medicine, 2023)
Coronary embolism is considered a rare non-atherosclerotic etiology of acute myocardial infarction, whereas atrial fibrillation is the main etiology of coronary embolism. We report a rare case of a patient with coronary embolism with a specific pearl-like embolus attributed to atrial fibrillation. For this patient, we used a balloon-based technique to successfully remove the embolus from the coronary artery.